Novel dealloying-fabricated NiCo2S4 nanoparticles with excellent cycling performance for supercapacitors. (25th March 2019) - Wang, Haiyang; Liang, Miaomiao; Ma, Chen; Shi, Wenyu; Duan, Dong; He, Gege; Sun, Zhanbo
Abstract: In this work, NiCo2 S4 nanoparticles for supercapacitors are successfully synthesized with a top-down strategy, using a novel dealloying method with an ion exchange reaction. The surface morphology and x-ray diffraction investigations demonstrated that NiCo2 S4 nanoparticles are interconnected by ligaments of the synthesized sample. The dealloyed NiCo2 S4 shows an enhanced electrochemical performance of about 1132.5 F g −1 at 0.5 A g −1 ; kinetic analysis implies a surface-controlled contribution from NiCo2 S4 (53.86% capacitive contributions). Notably, the NiCo2 S4 //AC (active carbon) device displays a comparatively high energy density (22.83 Wh kg −1 ), maximum power density (1327.1 W kg −1 ) and superior cycling performance (capacitance retention of 108% after 30 000 cycles).